Lychee disease management - Kumar, Manoj (Springer, 2017)
This book offers a comprehensive compilation of biotic and abiotic factors that affect lychee production and commercialization. It addresses disease management for a range of causal agents, including the leaf mite (Acerya litchi Keifer), leaf miner (Conopomorpha cramerella), fruit borers (Conopomorpha cramerella, Platypeplus aprobola Meyer and Dichocrosis sp.), leaf webber / roller (Platypepla aprobola Meyer), litchi bug (Tessarotoma javanica Thunb), bark-eating caterpillar (Indarbela quadrinotata) and shoot borer (Chlumetia transversa), etc. Specialized chapters highlight potential approaches to optimizing and increasing the scope of lychee export, as well as systematic research on the development and refinement of technologies for enhancing lychee productivity and quality. Further aspects addressed include post-harvest handling, processing and value addition, the development of tolerant varieties, high yield and processing. As such, 'Lychee Disease Management' offers a valuable resource dedicated to the global agriculture community, which is currently facing considerable production and commercialization problems.